Sistem Informasi Pengendalian Internal Pembelian Kredit Persediaan Barang Dagang pada Koperasi - Aryadi, Eki (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Implementation of activities in every company of course has a system that contains the procedures in its implementation. The purchase accounting system is an example of a system in a business used by the company to buy the necessary goods in this case the activities that the Honeymoon Services Corporation does to meet its supply of goods also by implementing the purchase system. The implementation of such a system of course requires a proper control system. The data used is data in the form of credit purchase information supplies and secondary data in supporting documents. In analyzing the data obtained using qualitative methods. The results of the writing of this scientific paper show that in the implementation of the system of purchase of supplies credit, the system applied by the Honey Gununung Cooperation has been sufficiently sound and efficient optimally with the presence of documents and systematic recording. Only in internal control still requires special attention especially the organizational aspects that have not focused on the key elements of internal control related to the separation of the main function where there is a part that captures the tasks performed by the receiving part that is captured as the storage of goods, which means.